Electric sampling of soot particles in spreading non-premixed flames: methodology and influence of gravity - Li, Yutao; Bordino, Antoine; Guibaud, Augustin; Montero, David; Citerne, Jean-Marie; Consalvi, Jean-Louis; Torero, Jose; Legros, Guillaume (Comptes Rendus. Mécanique, 2023)
Finer strategies of spacecraft fire mitigation require more experimental data related to fire detection. Fire detection systems developed on Earth rely massively on the optical detection of soot particles, which are present in the smoke. To detect the fire correctly, it is thus important to know how the optical properties of these particles are affected in reduced gravity. With different transport processes and increased residence time, soot in reduced gravity can be different from those produced at normal gravity. As their optical properties are related to their morphological properties, a better understanding about the evolution of soot particle morphology in flames under microgravity conditions is required. Within this context, a novel technique of soot sampling using electric field is applied to a spreading non-premixed flame at normal and micro-gravity. The soot particles sampled are observed subsequently under Transmission Electron Microscopy (TEM). Density, soot particle projected area, radius of gyration, fractal dimension, and primary particle size are extracted and the influence of gravity is investigated with the evolution of these morphological properties within the flame. Though the present study cannot be conclusive in itself, the similarity between the evolution of the optical density measured throughout the flame just before the electric perturbation required by the sampling technique and the evolution of the amount of soot deposited due to the electric perturbation along the sampling plates supports the future works that need to be devoted to further assess the consistency of the technique.